Effect of pelvic floor muscle training on female sexual function: A systematic review protocol and meta‐analysis - Carlos Saus‐Ortega; Ester Sierra‐Garcia; Antonio Martínez‐Sabater; Elena Chover‐Sierra; María Luisa Ballestar‐Tarín (Wiley, 2023)
Abstract Aim To recognize, appraise and summarize the research evidence that has explored the results of pelvic floor muscle training on female sexual function. Design Systematic review and possible meta‐analysis. Methodology Between September and October 2022, the Cochrane Library, CINAHL, MEDLINE, EMBASE, PsycINFO and Scopus electronic databases will be searched. We will include RCT's in English, Spanish and Portuguese that investigate the results of pelvic floor muscle training on female sexual function. The data will be extracted by two researchers independently. Risk of bias will be measured from the Cochrane Risk of Bias Tool. The meta‐analysis of the results will be performed using Comprehensive Meta‐Analysis Version 2. Results This systematic review and possible meta‐analysis will contribute significantly to the promotion of pelvic floor health and women's sexual function and to strengthen clinical practice and define other areas of study.